PROMOTION: A DIRECTION FOR HEALTH - Mercedes Trentini (Universidade Federal do Paraná, 1999)
This research project had the intend to answer the question: What do the health centers do in relation to the community health promotion? The conceptual framework consisted of the health promotion conceptualization according to the Octawa Chart. The sample consisted of 16 health centers and two policlinics centers. The results showed that the health promotion activities on public politics, environment, community action and personal abilities are undertaken in the health instituitions included in the sample.